PRADUGA TAK BERSALAH DAN TANTANGAN PENEGAKAN HUKUM DALAM KASUS KEKERASAN SEKSUAL TERHADAP PENYANDANG DISABILITAS TUNA GRAHITA - Titik Sri Astutik; Ratnaningsih (LPPM STIH Awang Long, 2026)
The presumption of innocence is a fundamental principle in the criminal justice system, ensuring that every individual is considered innocent until proven guilty by a legally binding court decision. However, the application of this principle faces serious challenges in cases of sexual violence, particularly when the victims are individuals with intellectual disabilities (tuna grahita) who experience double vulnerability, both physically, psychologically, and socially. This article aims to analyze how the presumption of innocence is implemented in law enforcement processes and the obstacles encountered when dealing with victims with intellectual disabilities. The research method used is normative juridical with statutory, conceptual, and case approaches. The findings indicate a tension between safeguarding the rights of suspects/defendants and the urgent need for maximum protection of vulnerable victims. The main challenges include limited legal accessibility, insufficient understanding of law enforcement officers regarding disability conditions, and the lack of evidence mechanisms sensitive to persons with intellectual disabilities. Therefore, more comprehensive legal policies are required to balance the presumption of innocence and victim protection principles, through regulatory strengthening, capacity building for law enforcement, and the provision of special assistance for victims with disabilities.